Analisis manajemen risiko pembiayaan dalam menekan NPF pada perbankan syariah: Pendekatan literatur berbasis POJK No. 65/2016 - Agustina, Nurlaila Tria (Maliki Interdisciplinary Journal, 2026)
This study aims to examine financing risk management in an effort to reduce the level of Non-Performing Financing (NPF) in Islamic banking, referring to OJK Regulation No. 65/POJK.03/2016. The study results indicate that financing risk is the primary risk due to its direct link to the bank’s intermediation function and asset quality. The implementation of risk management, which encompasses the stages of identification, measurement, monitoring, and control, is in principle in line with OJK regulations. However, its implementation remains suboptimal due to limitations in early risk detection and ineffective financing oversight. Risk mitigation efforts are carried out through the application of prudential principles, increased active supervision, and restructuring of problem financing as the primary strategy to reduce the NPF level and maintain asset quality. Overall, the effectiveness of financing risk management impacts profitability, stability, and public trust. Therefore, strengthening the implementation of risk management based on regulations and Sharia principles is a crucial factor in maintaining the sustainability of Islamic banking.